Chronic thromboembolic pulmonary hypertension: Reversal of pulmonary hypertension but not sleep disordered breathing following pulmonary endarterectomy. (1st August 2018) - La Rovere, Maria Teresa; Fanfulla, Francesco; Taurino, Anna Eugenia; Bruschi, Claudio; Maestri, Roberto; Robbi, Elena; Maestroni, Rita; Pronzato, Caterina; Pin, Maurizio; D'Armini, Andrea M.; Pinna, Gian Domenico
Abstract: Background: It has been hypothesized that pre-capillary pulmonary hypertension (PH) may trigger sleep disordered breathing (SDB). In patients with chronic thromboembolic PH (CTEPH), pulmonary endarterectomy (PEA) is potentially effective to improve PH. We assessed the pre- and post-operative prevalence of SDB in CTEPH patients submitted to PEA and the relationship between SDB and clinical, pulmonary and hemodynamic factors. Methods: Unattended cardiorespiratory recording was performed the night before and one month after elective PEA in 50 patients. Results: Before the intervention SDB prevalence (obstructive or central AHI ≥ 5/h) was 64%: 18 patients (66% female) had No-SDB, 22 (68% female) had dominant obstructive (dOSA), and 10 (20% female) had dominant central sleep apnea (dCSA). There were no differences in risk factors and the need for supplemental oxygen. Mean right atrial (mRAP) and pulmonary artery pressures (mPAP) showed a more compromised profile from No-SDB to dOSA and dCSA (mRAP: 5.5 ± 3.9 vs 7.0 ± 4.5 vs 9.7 ± 4.3 mm Hg (p = 0.054), mPAP: 39 ± 12 vs 48 ± 11 vs 51 ± 16 mm Hg (p = 0.0.47)). By contrast, cardiac index did not differ. At post-intervention, the prevalence of SDB was 68%: 16 patients had No-SDB, while 30 had dOSA and 4 dCSA, with no relationship with the relief from PH. Interestingly, 5 patients with previous CSA moved to the OSA group and 2 normalized. Conclusions: Prevalence of SDB is high in patients with CTEPH even after resolution of PH. Our data support the hypothesis that pre-capillary PH may trigger CSA but not OSA, and suggest that OSA may play a role in the development of CTEPH. Highlights: OSA is highly prevalent in patients with CTEPH after successful pulmonary endarterectomy. Obstructive sleep apnea may play a role in the development of chronic thromboembolic pulmonary hypertension. The hemodynamic impairment associated with CTEPH may trigger CSA. Sleep studies are recommended in patients with CTEPH.